2012
DOI: 10.1016/j.ijgo.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the complete ban on female genital cutting on the attitude of educated women from Upper Egypt toward the practice

Abstract: The decrease in prevalence of FGC after its complete ban was small after 5 years, with little change in attitude among educated families in Upper Egypt. In addition to the current law, a change in attitude will be needed to wipe out this custom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
2
22
0
1
Order By: Relevance
“…The reasons the Egyptians reported the most for their decision to have FGM/C performed on their daughters were family pressure (42.6%), religious obligations (38.3%), and the preservation of their daughters' chastity (19.0%) [17].…”
Section: Types Of Fgmmentioning
confidence: 99%
“…The reasons the Egyptians reported the most for their decision to have FGM/C performed on their daughters were family pressure (42.6%), religious obligations (38.3%), and the preservation of their daughters' chastity (19.0%) [17].…”
Section: Types Of Fgmmentioning
confidence: 99%
“…According to Bonessio (as cited in Ref. [24], p. 275), "education level is a major independent factor of change in attitude" in terms of FGM. This statement is supported by the findings of several studies (UN, Klouman; Msuya; Snow, as cited in Ref.…”
Section: Individual Levelmentioning
confidence: 99%
“…Afifi et al (as cited in Ref. [24]) found that women with higher education level who were empowered within their social context were up to 8.06 times more likely to decide not to perform FGM on their daughters. Mudege et al [25] and Karmaker et al [21] suggested that the education level of parents was a good predictor for letting their daughters undergo FGM or not.…”
Section: Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt, the percentage of women who had any procedure that altered external genitalia performed on a daughter only fell from 77.8% to 71.6% over 5 years from 2006 to 2011. This relatively small decrease in prevalence was associated with minimal change in attitude towards the procedures 6. In a study in Somalia, the country in the world with the highest prevalence of these procedures, 81% of subjects underwent infibulation and only 3% did not have FGA.…”
mentioning
confidence: 96%